Digital Marketing Strategy at XYZ Bank - Trissetianto, Andri Catur; Ridwan (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
In the rapidly evolving digital era, banking institutions are required to adapt their marketing strategies to meet the changing behavior and expectations of consumers. This study aims to analyze the digital marketing strategies implemented by Bank XYZ and evaluate their impact on customer experience, engagement, and overall business performance. Using a qualitative case study approach, data were collected through interviews with marketing and IT staff, focus group discussions with customers, and the review of internal documents and digital analytics. The findings reveal that Bank XYZ utilizes a comprehensive digital marketing approach involving social media platforms, SEO, targeted email campaigns, paid online advertising, and mobile application promotion. These strategies have contributed significantly to enhancing the digital customer experience by offering personalized content, real-time services, and interactive features. As a result, there has been a notable increase in customer engagement and satisfaction, which positively influenced key business metrics such as customer acquisition, retention, and brand perception. Despite these successes, the study identifies several areas for improvement, including the need for enhanced personalization across channels, stronger integration between departments, and improved cybersecurity measures. This research provides practical insights for financial institutions seeking to optimize digital marketing practices and emphasizes the importance of customer-centric, data-driven strategies in maintaining competitiveness in the digital banking landscape.